A web‐based survey on the occurrence of emotional blunting in patients with major depressive disorder in Japan: Patient perceptions and attitudes - Toshiaki Kikuchi; Jun‐ichi Iga; Masato Oosawa; Tatsuya Hoshino; Yoshiya Moriguchi; Miwa Izutsu (Wiley, 2024)
Abstract Aims To determine the prevalence and impact of emotional blunting (EB) in patients with major depressive disorder (MDD) in Japan, and identify treatment needs for EB using patients' perceptions and attitudes. Methods Eligible patients in Japan (aged 18-59 years) who reported a diagnosis of MDD and antidepressant medication use for >3 months were eligible to complete an online survey. The primary outcome was the prevalence of EB, self‐reported using a validated screening question. Secondary outcomes included the correlation between EB symptoms (measured by the Oxford Depression Questionnaire [ODQ]) and scores on the Patient Health Questionnaire 9‐item (PHQ‐9), Generalized Anxiety Disorder 7‐item (GAD‐7), Work and Social Adjustment Scale (WSAS), and the EuroQol 5‐Dimension 5‐Levels questionnaire (EQ‐5D‐5L). Descriptive questions were used to explore patients' perceptions and attitudes toward EB. Results In total, 3376 patients were included in the analysis (56% male; 48% aged 50-59 years). Overall, 67.1% of patients self‐reported symptoms of EB, with 10% rating these as severe. The mean (SD) ODQ total score was 78.2 (21.5), which increased with worsening EB symptoms. There were correlations between ODQ total scores and the PHQ‐9, GAD‐7, WSAS, and EQ‐5D‐5L scores (correlation coefficients: 0.67, 0.55, 0.56, −0.51, respectively; all p < 0.0001). Descriptive analyses showed that one‐third of patients reporting EB symptoms did not tell their physician, with two‐thirds finding these symptoms distressing and likely to affect recovery. Conclusion EB is an important clinical issue in Japan that needs to be considered alongside functional recovery when managing treatment of patients with MDD.